Upravljanje stresnih emocij na delovnem mestu - Pavlič, Jerca (Družboslovne razprave, 2019)
The article deals with work-related stress that ever more employees experience in the modern business world. The article criticises the discourse of the individualisation of stress, which states that employees must construct themselves as individuals and shape their own reality beyond the scope of broader collectivism. The authors set the model of managing stress emotions at a group level and deal with the concept of a group emotional culture, which enables employees to be more successful and effective in coping with stress by using group emotional norms, strategies, rituals and routines and cultural artefacts. The article focuses on the problems of growing work-related stress, which ought to be characterised as an organisational problem and dealt with on a primary, secondary and tertiary level.
Keywords: Čustva; Delovni stres; Delovno mesto; Emotions; Individualizacija; Individualization; Job stress; Workplace